PENGARUH LAYANAN TAHAPAN DAN ATM BCA TERHADAP KEPUASAN NASABAH BANK BCA CABANG ROXY MAS JAKARTA - Rhoma Iskandar; Muhamad Ihwanudin (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2022)
Customer service plays a very important role in a business. In addition to the products or services offered by customers, they will also definitely assess the way employees serve them, customer services will not go unnoticed by customers. Business founders are obligated to provide product and services that are able to provide satisfaction to customers.Along with economic and technological developments as well as business competition, companies compete to be able to provide more satisfying products and services for customers.This is done in order to get new customers and retain customers. This study aims to determine the effect of service quality and product quality on customer satisfaction. The population used in this study is customers of BCA cabang Roxy Mas. Data collection methods using library research and field research. As for the analysis technique used in this study is multiple correlation coefficient analysis. The test results show that the variables used in this study have a significant and positive effect on customer satisfaction of BCA cabang Roxy Mas. This indicates that the better the quality of service, the more customer satisfaction increases.